PENANAMAN NILAI-NILAI NASIONALISME MELALUI PENDIDIKAN AGAMA PADA SEKOLAH MENENGAH ATAS DI PERBATASAN NEGARA: IMPLEMENTASI DI SMAN 1 JAGOIBABANG KABUPATEN BENGKAYANG PROVINSI KALIMANTAN BARAT: CULTIVATING NATIONALISM VALUES THROUGH RELIGIOUS EDUCATION IN SENIOR HIGH SCHOOL AT PERBATASAN NEGARA: IMPLEMENTATION AT SENIOR HIGH SCHOOL (SMAN) 1 JAGOIBABANG BENGKAYANG WEST KALIMANTAN - A.M. Wibowo (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
This study aims to describe the cultivation of nationalism values through religious education to Senior High School students in the area of Perbatasan Negara which include: (1) the implementation of cultivating nationalism among senior high schools students in the area of Perbatasan Negara; (2) the nationalism behavior of senior high schools students in in the area of perbatasan negara; (3) supporting and inhibiting factors of cultivating nationalism through religious education for senior high school students in in the area of Perbatasan Negara. Using qualitative research methods, this study managed to find three findings: (1) Nationalism values has been implemented in high schools in in the area of Perbatasan Negara both it is implied or declared in religious education curriculum; (2) Regarding cognitive domain, students have understood nationalism values that have been taught by their religion teachers. In terms of affective aspect, most students have affectively practiced religion teaching about nationalism, and in psychomotor aspects, students have to have a spirit of nationalism such as the use of Indonesian language in their daily life at school; (3) The internal supporting factors of cultivating nationalism are through religious education is religious teachers competence and school culture, while the external supporting are through curriculum and extracurricular activity, Pramuka. The internal inhibiting factors of cultivating nationalism are through religious education aspects, including learning environment, and the absence of religious handbooks for students. The external the inhibiting factors in cultivating their nationalism values and nationality are family background, environmental conditions, and government policies.Keywords: Nationalism, religious education, Perbatasan Negara, West Kalimantan. Penelitian ini bertujuan mendeskripsikan tentang penanaman nilai-nilai nasionalisme melalui pendidikan agama pada peserta didik Sekolah Menengah Atas di daerah Perbatasan Negara yang meliputi: (1) implementasi penanaman nasionalisme pada peserta didik di SMA di wilayah Perbatasan Negara, (2) perilaku nasionalisme peserta didik SMA di daerah Perbatasan Negara, (3) faktor pendukung dan penghambat penanaman nasionalisme melalui pendidikan agama pada peserta didik SMA di daerah perbatasan negara. Dengan menggunakan metode penelitian kualitatif penelitian ini berhasil menemukan 3 temuan, yaitu: (1) nilai-nilai nasionalisme telah diimplementasikan pada SMA di Perbatasan Negara, baik disisipkan maupun secara khsusus dalam kurikulum pendidikan agama; (2) secara kognitif, peserta didik telah memahami nilai-nilai nasionalisme yang telah diajarkan oleh guru agama mereka, secara afektif sebagian peserta didik telah mengamalkan ajaran agama tentang nasionalisme sebagian lagi belum, dan secara psikomotorik peserta didik telah memiliki jiwa nasionalisme seperti menggunakan bahasa Indonesia dalam pergaulan sehari-hari di sekolah; (3) faktor internal pendukung penanaman nasionalisme melalui pendidikan agama adalah kompetensi guru agama dan budaya sekolah, secara eksternal faktor, pendukung penanaman nasionalisme melalui kurikulum dan ekstrakurikuler Pramuka. Faktor internal, penghambat penanaman nasionalisme melalui pendidikan agama meliputi lingkungan belajar dan ketiadaan buku-buku agama pegangan untuk peserta didik. Secara eksternal, pengambat penanaman nilai-nilai nasionalisme dan kebangsaan peserta didik adalah latar belakang keluarga, kondisi lingkungan sekitar, dan kebijakan pemerintah.Kata Kunci: Nasionalisme, pendidikan agama, Perbatasan Negara, Kalimantan Barat.